Total neoadjuvant therapy or standard chemoradiotherapy for locally advanced rectal cancer: A systematic review and meta-analysis - Ma, Zhou; Tan, Ling; Liu, Zi-lin; Xiao, Jiang-wei (Frontiers in Surgery, 2022)
Background and Aim The effectiveness of total neoadjuvant therapy (TNT) on patients with locally advanced rectal cancer (LARC) is controversy. This study aims to compare the prognostic value of TNT with standard neoadjuvant chemoradiotherapy (CRT) for LARC. Methods We searched databases (Embase [Ovid], Medline [Ovid], PubMed, Cochrane Library, and Web of Science) for articles published between January 1, 2000, and March 10, 2022. Studies on evaluating the effects of TNT and standard CRT on the prognosis of LARC were included. The primary outcomes were overall survival (OS) and disease-free survival (DFS). Results 19 primary studies, involving 10 randomized controlled trials ,3 prospective studies and 6 retrospective studies, with data on 5074 patients treated for LARC were included in the meta-analysis. Statistical analyses revealed that, compared with standard CRT, TNT significantly improved OS (hazard ratio [HR] = 0.77, 95% confidence interval [CI] = 0.65-0.90, I2 = 30%, P = 0.17), DFS (HR = 0.85, 95% CI = 0.74-0.97, I² = 11%, P = 0.35), distant metastases free survival (DMFS, HR = 0.76, 95% CI = 0.65-0.90, I²= 0%, P = 0.50), pathological complete response rate (pCR, OR = 1.89, 95% CI = 1.61-2.22, I² = 0%, P = 0.47), and R0 resection rate (OR = 1.33, 95% CI = 1.07-1.67, I²= 16%, P = 0.28), but local recurrence-free survival (LRFS, HR = 1.12, 95% CI = 0.90-1.39, I² = 4%, P = 0.37). Conclusions Comprehensive literature research shows that TNT showed excellent short-term efficacy in terms of pCR and R0 resection rate while also improved the long-term outcomes of OS, DFS and DMFS, might become a new standard of treatment in patients with LARC. Even so, more studies and longer follow-up were still warranted.